Biosocial variables and auditory acuity as risk factors for non-fatal childhood injuries in Greece. Issue 2 (June 1995) - Petridou, E.; Zervos, I.; Christopoulos, G.; Revinthi, K.; Papoutsakis, G.; Trichopoulos, D.
Abstract : OBJECTIVES: To examine whether biosocial variables and auditory acuity are risk factors for injuries among children. SETTING: Children with injuries who presented at the emergency clinics of one of the two university hospitals for children in Athens, Greece between December 1993 and April 1994. METHODS: 144 children aged 5-14 years, residents of Athens, were brought to the emergency clinics for a moderate to severe injury. For each of these children one hospital control, matched for age and sex, and one classmate control similarly matched were identified. A standard interview form was completed for all 432 children and acouometric and tympanometric examinations were performed in each of them. Analysis was done through conditional logistic regression. RESULTS: The likelihood of an accident was higher in children of younger fathers (odds ratio (OR) = 0.7, p = 0.04), children of mothers with non-professional jobs (OR = 1.9, p = 0.03) as well as in children of higher birth order (OR = 1.7, p = 0.01), in those with predominantly other than parental daily supervision (OR = 2.6, p = 0.001), and those with a history of previous accident (OR = 1.3, p = 0.002). Somatometric factors, school performance, use of corrective eyeglasses and subnormal auditory acuity were not found to be risk factors, but auditory imbalance and abnormal tympanograms were positively related to the risk of childhood injury (OR = 2.6, p = 0.02; and OR = 2.3, p = 0.08 respectively). CONCLUSIONS: the findings of this study underline the importance of attentive supervision and safety training of children living in modern cities; they also suggest that children with auditory imbalance and history of an accident are at higher injury risk and they should be targeted with specific intervention programs.